Caregivers' perceptions of the Baby Mat Project. - Aspoas, Belinda (My University, 2013)
This study set out to investigate the parent-infant interventions that are run by a community-based organisation on the outskirts of Johannesburg’s Alexandra township, South Africa. Community-based interventions that support the parent-infant dyad present an ideal opportunity to shape the development of youth as they aim to foster secure attachment relationships thereby providing the bedrock for future growth. This research specifically explores caregivers’ perceptions of the Baby Mat project in order to understand why some caregivers make optimal use of this intervention whereas others do not. It also gives insight into why some caregivers who are referred for parent-infant psychotherapy on the Baby Mat fail to take up this offer. In addition, it identifies needs caregivers have that are not being met by the Baby Mat. Data for this study was collected by holding a focus group with 11 caregivers in group discussion. The results of the data analysis indicate that caregivers are increasingly having to navigate the transition to motherhood alone, and are often overwhelmed with anxiety. Possibly this is because the support gleaned from extended families has diminished over the last few decades in South Africa. Consequently caregivers are often very receptive to the Baby Mat, which they see in the role of “grandmother”. By visiting the Baby Mat, caregivers realise that they are not alone in the challenges they face and often leave the mat feeling more hopeful about their problems. Yet several factors block them from making full use of this intervention. The primary one is their socially and economically weak position. They are also concerned that actions that they would rather avoid might be taken when facilitators on the mat learn of the abuse they are exposed to. Having limited resources, they are often looking for information and guidance and when this need cannot be met, frustration follows. Generally they want people running relevant interventions to come to them, as opposed to their going out to seek support. This may explain their failure to take up parent-infant psychotherapy. It is also was evident that the caregivers want to reach out to each other.
Keywords: Caregiver-infant dyad; Community-based prevention; Parent-infant psychotherapy; Baby Mat project; Attachment in South Africa; Facilitating reflective functioning; Caregivers in South Africa